Diagnostic performance of point-of-care ultrasonography (POC-US) in haemophilia joint health: a comparative study with MRI - Duseja Yash; Kashyap Arnav; Dutta Anupam; Borpatragohain Dhrubajyoti; Dhal Bhabani; Borboruah Luish (The Journal of Haemophilia Practice)
Haemophilia presents challenges in joint pathology assessment, prompting exploration of point-of-care ultrasonography (POC-US) as a diagnostic tool. Aims: The study aimed to assess the diagnostic performance of point-of-care ultrasonography (POC-US) compared to magnetic resonance imaging (MRI) in detecting synovial hypertrophy, cartilage abnormality, and bony abnormality among people with haemophilia (PWH) treated at Assam Medical College Hospital.